Some Formulae of Products of the Apostol-Bernoulli and Apostol-Euler Polynomials - Yuan He; Chunping Wang (Discrete Dynamics in Nature and Society)
Some formulae of products of the Apostol-Bernoulli and Apostol-Euler polynomials are established by applying the generating function methods and some summation transform techniques, and various known results are derived as special cases.